Weighted estimates for a class of rough singular integrals(关于一类奇异积分算子的加权有界性) - CHENQiong-lei(陈琼蕾) (Zhejiang Daxue xuebao. Lixue ban, 2004)
Fourier估计和Littlewood-Paley理论，证明了 Rn上一类带粗糙核的奇异积分算子的的（，LP(ω）)有界性，推广了已有的结果.这里Ω为Hardy空间Hq(sn-1)中的函数，，且满足适当的积分消失条件，b(|y|)为L∞函数，ω为某类径向权，α为非负整数.is (,LP(ω)) bounded. Here b(|y|) Є L∞(Rn) ，Ω is a function of Hardy space Hq(sn-1) satisfying a suitable cancellation condition, , ω is a class of radial weights， and α is a nonegative integer. This is a generalization of the known result.